2019
DOI: 10.1016/j.semnephrol.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Features of Ammonia Metabolism and Transport in Acid-Base Balance

Abstract: Ammonia metabolism has a critical role both in acid-base homeostasis and in other cellular functions. Kidneys have a central role in bicarbonate generation, which occurs through the process of net acid excretion; ammonia metabolism is the quantitatively greatest component of net acid excretion, both under basal conditions and in response to acid-base disturbances. Several recent studies have substantially advanced our understanding of the molecular mechanisms and regulation of ammonia metabolism. First, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 97 publications
(109 reference statements)
0
21
0
Order By: Relevance
“…Certainly, bTRPV3 is not the only NH 4 + transporting channel and there is good reason to believe that in the rumen, in Xenopus oocytes, and in other parts of the gut, multiple types of non-selective cation channels should be considered when searching for pathways for the uptake of ammonium [58].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, bTRPV3 is not the only NH 4 + transporting channel and there is good reason to believe that in the rumen, in Xenopus oocytes, and in other parts of the gut, multiple types of non-selective cation channels should be considered when searching for pathways for the uptake of ammonium [58].…”
Section: Discussionmentioning
confidence: 99%
“…Rh glycoproteins Rhbg and Rhcg are the primary proteins that mediate collecting duct ammonia secretion, and their expression generally parallels changes in ammonia excretion (10,16,52). However, KS-AR-KO did not alter significantly Rhbg protein expression in either male or female KS-AR-KO mice in either the cortex or inner stripe of the outer medulla (Fig.…”
Section: Effect Of Kidney-specific Ar Deletion On Ammonia Transportersmentioning
confidence: 91%
“…NKCC2 mediates TAL ammonia reabsorption (10,16,52). In male mice, KS-AR-KO increased NKCC2 protein expression using immunoblot analysis significantly; in female mice, there was no significant change (Fig.…”
Section: Effect Of Kidney-specific Ar Deletion On Ammonia Transportersmentioning
confidence: 92%
See 1 more Smart Citation
“…The study revealed changes in glutamine metabolism (i.e., higher plasma glutamine and γ-glutamyl-glutamine levels in fearful vs. non-fearful dogs). The essential AA glutamine serves not only as a precursor for the neurotransmitter glutamate, the most abundant and primary excitatory neurotransmitter in the central nervous system, but also for the neurotransmitter GABA [39], for antioxidant glutathione [40], protein, nucleotide and nucleic acid synthesis [41], as a substrate for gluconeogenesis [41] and ammonia genesis [42]. Glutamine actions in the brain are mostly mediated by the degradation of glutamine to glutamate as a part of the glutamate-glutamine cycle [39].…”
Section: Metabolomics In Anxiety Modelsmentioning
confidence: 99%